2018
DOI: 10.1186/s12871-018-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

Dental injury in anaesthesia: a tertiary hospital’s experience

Abstract: BackgroundDental injury is a common perioperative complication, but there are no country specific data available, especially with the use of supraglottic airway devices (SAD). The aims of our study are to report the incidence, risk factors, and local practices in the management of perioperative dental injuries in Singapore.MethodsWe analyzed data from the departmental database from 2011 to 2014, noting the anticipated difficulty of airway instrumentation, intubation grade, pre-existing dental risk factors, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…In that study, supraglottic airway devices accounted for 15% of the claims. This has also been shown in another study where 14% of dental injuries occurred after the use of supraglottic devices …”
Section: Discussionsupporting
confidence: 76%
“…In that study, supraglottic airway devices accounted for 15% of the claims. This has also been shown in another study where 14% of dental injuries occurred after the use of supraglottic devices …”
Section: Discussionsupporting
confidence: 76%
“…It should be considered that dental trauma may be caused by the initial trauma or may be iatrogenic especially after endotracheal intubation [ 23 , 24 ]. It was identified that existing dental anomalies increases the risk for dental injury by endotracheal intubation in a 12-fold manner [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 23 references meeting the selection criteria were included. 7-29 A flow diagram detailing this process is shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%